Novelization of the provisions of the criminal legislation of Ukraine, which provide for liability for medical crimes and misdemeanors: issues of interpretation and enforcement - Grynchak, Serhii; Grynchak, Alla A. (Problems of legality, 2024)
The problems of criminal law protection of life and health of a person in the field of medical care attract the special attention of scientists, because it is about the most valuable constitutional rights and freedoms of a person. At the same time, the results of the analysis of criminal statistics regarding registered medical crimes and misdemeanours, their further pretrial investigation and trial, give grounds for serious concern. The reasons for the negative investigative and judicial practice may be the shortcomings of the legal construction of the norms, numerous changes made to the Criminal Code, as well as the high latency of medical offenses. Therefore, the purpose of this article is a comprehensive study of the amendment of the criminal legislation of Ukraine, which provides for responsibility for medical offenses, identifying the shortcomings and advantages of such legislative decisions, as well as formulating separate recommendations for the enforcement of the norms of the Criminal Code. The following research methods were used to achieve the specified goals. The dialectical method of cognition made it possible to establish the norms of the Criminal Code of Ukraine, which provide for responsibility for medical offenses and to reveal the problems of their enforcement. The historical method made it possible to identify all normative acts that amended the norms of the Criminal Code, which provide for liability for medical offenses. The dogmatic method made it possible to clarify the true content of such concepts as "order of application of transplantation", "activity connected with transplantation", " substantial harm to the victim's health", etc. The systemic-structural method was used to analyse such evaluative concepts as "damage to the victim's health", " substantial damage to the victim's health", "severe consequences", etc., which are used in many provisions of the Criminal Code and are interpreted in different ways in judicial practice. The comparative legal method was used to compare the regulatory national legislation of Ukraine in the field of medical care and the relevant norms of the Criminal Code of Ukraine. The conducted research gave grounds for the conclusion that socially dangerous consequences in the form of "substantial harm to the victim's health", which are provided for in Part 1 of Art. 143 of the Criminal Code, cover the infliction of light physical injuries on the victim that caused a short-term health disorder or minor loss of working capacity, moderate physical injuries, severe physical injuries, as well as infection with the human immunodeficiency virus or other incurable infectious disease. At the same time, negligently causing the death of a recipient during an illegal transplantation requires additional qualification under a set of criminal offenses. The revealed cases of arbitrary and sometimes unsystematic use of different evaluation concepts of harm to human health in the norms of the Special Part of the Criminal Code point to the urgent need for unification in the criminal legislation of Ukraine, both the concept of "harm to health" and the normative consolidation of its types.